RUPAFENDER: safety boot shoe sole / Noor Aishatun Majid ... [et al.] - Majid, Noor Aishatun; Abdul Rahman, Wahida; Fadzid, Muhammad Saifullah; Abdul Razak, Fatimatuzzahrah; Jamal, Siti Noorashikin; Dulilah, Mohammad Noor Azmi; Mohamad Idris, Muhammad Irfan; Majid, Mohamad Azamuddin (2020)
RuPaFENDER is an innovation on shoe sole part of safety boot with flame retardant property. It had been derived from polyvinyl chloride (PVC)/acrylonitrile butadiene rubbers (NBR) composites with silane coupling agent treated palm kernel shell powder (Si-PKS) filler. Carbon black derived petroleum based as filler in the existing shoe sole rubber composites caused the fluctuation of material cost. Therefore, Si-PKS had been found to be the best option for the substitution of carbon black in making shoe sole. Besides, the usage of Si-PKS also able to solve environmental issues that created by abundant palm kernel shell waste during palm oil production. This product able to offer better tensile strength and swelling resistance, better flame resistance with low cost.